Analysis of the Success of Religious Courts in Reducing the Number of Marriage Dispensations as an Effort to Support the Government in Preventing Child Marriage - Ahmad Yusroni; Bambang Santoso Haryonk; Mohammad Nuh (Faculty of Law, Universitas Pekalongan, 2023)
Dispensation for marriage is actually considered a simalakama fruit, because changes to the age limit for marriage seem futile if in the end minors can legally marry with dispensation from the Court. The facts on the ground show that the ambiguity in Article 7 of Law No. 16/2019 on Marriage leaves more serious problems. As a result, several court institutions have been flooded with applications for dispensation for various reasons submitted by parents of children who wish to marry. Malang District, which contributed the highest number of marriage dispensations in East Java in 2022, has conducted various policy programs that have succeeded in reducing the number of marriage dispensations. This article analyzes the success of the Religious Court in reducing the number of marriage dispensations as an effort to support the government in preventing child marriage and what the level of success is by using descriptive qualitative research methods with Allan McConnell's Policy Success theory. This article explores the success of preventing child marriage from the program dimension and its level of success. The results showed that in the indicator of implementation according to the objectives, the level of success was included in Success. Meanwhile, in the indicator of achieving the expected results, the level of success is included in Resilient Success because although there is a decrease in applications for marriage dispensation every year, the number is still high. And finally, the indicator provides benefits to the target group, the level of success is included in Success.